Cooperative Social Balance. Case: Farm Service Cooperative La Trinidad S. R. L., 2004 - García Müller, Gerardo (Cooperativismo & Desarrollo, 2013)
This paper synthesizes some results of research carried out between 2002 and 2004 at Cooperativa de Servicios Agrícolas La Trinidad of Pueblo Llano, Estado Merida, Venezuela, by the undersigned in support of his doctoral thesis research at the Universidad de Granada. The aim of the research was to assess of compliance with the cooperative principles, using the methodology of the Social Cooperative Balance. The method chosen, “Balance of Cooperative Identity”, was developed by Dr. Aitziber Mugarra of the Universidad de Deusto, Spain, in 1998. The evaluation was made on the implementation of the seven cooperative principles. To do this each of the principles was operationalized taking it as a variable, then dividing it into sub-variables or dimensions and each of the latter were separated in social indicators, expressed in physical, monetary or qualitative way.